Pre-plaque Aß-Mediated Impairment of Synaptic Depotentiation in a Transgenic Rat Model of Alzheimer’s Disease Amyloidosis - Qi, Yingjie; Klyubin, Igor; Hu, Neng-Wei; Ondrejcak, Tomas; Rowan, Michael J. (Frontiers in Neuroscience, 2019)
How endogenously produced soluble amyloid ß-protein (Aß) affects synaptic plasticity in vulnerable circuits should provide insight into early Alzheimer’s disease pathophysiology. McGill-R-Thy1-APP transgenic rats, modeling Alzheimer’s disease amyloidosis, exhibit an age-dependent soluble Aß-mediated impairment of the induction of long-term potentiation (LTP) by 200 Hz conditioning stimulation at apical CA3-to-CA1 synapses. Here, we investigated if synaptic weakening at these synapses in the form of activity-dependent persistent reversal (depotentiation) of LTP is also altered in pre-plaque rats in vivo. In freely behaving transgenic rats strong, 400 Hz, conditioning stimulation induced stable LTP that was NMDA receptor- and voltage-gated Ca2+ channel-dependent. Surprisingly, the ability of novelty exploration to induce depotentiation of 400 Hz-induced LTP was impaired in an Aß-dependent manner in the freely behaving transgenic rats. Moreover, at apical synapses, low frequency conditioning stimulation (1 Hz) did not trigger depotentiation in anaesthetized transgenic rats, with an age-dependence similar to the LTP deficit. In contrast, at basal synapses neither LTP, induced by 100 or 200 Hz, nor novelty exploration-induced depotentiation was impaired in the freely behaving transgenic rats. These findings indicate that activity-dependent weakening, as well as strengthening, is impaired in a synapse- and age-dependent manner in this model of early Alzheimer’s disease amyloidosis.